Frequency And Unusual Clinical Manifestation Of Orbital Xanthogranulomas: An Overview - Manzoor, Amna; Taimur, Fariha; Saad, Muhammad; Ahmad, Saadullah; Tahir, Faizan; Khan, Sumeya (Journal of Rawalpindi Medical College, 2024)
Objective: To assess the frequency and clinical characteristics of orbital xanthogranulomas, focusing on their unusual presentations and impact on bone structure in a South Asian population. Methods: This is a retrospective study conducted at Al-Shifa Trust Eye Hospital, a tertiary care hospital in Rawalpindi, Pakistan. The study included patients diagnosed with orbital xanthogranulomas between July 2001 and July 2023. The variables collected included patient demographics (age, gender), presenting symptoms, duration of symptoms before presentation, clinical features, diagnostic modalities used (e.g., CT scans, histopathology), treatment modalities, and follow-up outcomes. Results: Between July 2001 and July 2023, 1250 orbital lesions were identified. Out of these, a total of 6 patients were diagnosed with orbital xanthogranuloma. The presenting symptoms for these 6 patients included proptosis in 5 cases, loss of vision in 5 cases, and redness of the eyes in 1 case. In four patients, bony erosions were seen preoperatively. The most commonly involved bone was the roof of the orbit. In one patient, osteosclerosis of the knee and elbow joint was reported. The mean duration of symptoms before presentation was 1.8 years, ranging from 3 months to 5 years. The mean age at presentation was 38 years (range, 3 – 70 years). Recurrence was seen in only one patient. Conclusion: In conclusion, our findings indicate that orbital xanthogranulomas, while rare, constitute a noteworthy proportion of lesions with bony erosions. These tumours manifest with diverse clinical features, complications, and systemic associations, making them complex to diagnose and manage effectively.